COMPETITIVENESS AND INFLUENCING FACTORS INDONESIAN COCOA BEAN EXPORTS IN THE INTERNATIONAL MARKET - Waruwu, Jernih Wati; Simanullang, Endang Sari (Institute of Computer Science (IOCS), 2025)
Indonesia is known as an agricultural country. This is because the majority of Indonesia's population lives in rural areas and works in the agricultural sector. Indonesia is one of the countries that participates in international trade. This research aims to 1) analyse the competitiveness of Indonesian cocoa bean exports in the international market, 2) analyse the factors that influence the value of Indonesian cocoa bean exports in the international market. This research has 5 destination countries, namely Malaysia, Belgium, Singapore, India and the United States. The research method used to analyse competitiveness is Revealed Comparative Advantage (RCA) which is used to determine dynamic competitive performance or not. Meanwhile, in analysing the factors that influence the value of Indonesian cocoa bean exports, an analysis method using panel data regression was used using Eviews 12 software. The results of this research show that Indonesia has a strong comparative advantage in cocoa bean exports. This is indicated by the average RCA value being greater than 1 for all destination countries. Meanwhile, the factors that influence cocoa bean exports with production variables and export prices significantly have a positive effect on the value of Indonesian cocoa bean exports on the international market. The Rupiah Exchange Rate and GDP variables have a negative influence on the value of Indonesian cocoa bean exports on the international market, but the significance of the influence needs to be studied in more depth.